What to put on and what to keep off the Table? A Politician's Choice of which Issues to address - Rei S. Sayag; Otto H. Swank (Tinbergen Institute, 2012)
At the start of their term, politicians often announce which issue they intend to address. To shed light on this agenda setting, we develop a model in which a politician has to decide whether or not to address a public issue. Addressing an issue means that the politician investigates the issue and next chooses for either a major reform or a minor reform. Not addressing an issue means that the status quo is maintained. Politicians differ in their ability to make correct decisions. They want to make good decisions and want to come across as able decision makers. An important characteristic of the model is that politicians and voters have different priors concerning the desirability of a major reform. We show that electoral concerns may lead to anti-pandering. Politicians tend to put issues on their political agenda when voters are relatively pessimistic about a major reform, and keep issues off the table when voters are optimistic about major reform.
urn:NBN:nl:ui:15-1765/38212
Keywords: D72; D78; D82; P16; 330; Agenda Setting; Career concerns; Pandering; Interessenpolitik; Politische Entscheidung; Karriereplanung; Politiker; Asymmetrische Information; Neue politische Ökonomie